Function of quorum sensing and cell signaling in wastewater treatment systems - Huizhi Hu (IWA Publishing, 2021)
Quorum sensing (QS) is a communication mode between microorganisms to regulate bacteria ecological relations and physiological behaviors, thus achieve the physiological function that single bacteria cannot complete. This phenomenon plays important roles in the formation of biofilm and granular sludge, and may be related to enhancement of some functional bacteria activity in wastewater treatment systems. There is a need to better understand bacterial QS in engineered reactors, and to assess how designs and operations might improve the removal efficiency. This article reviewed the recent advances of QS in several environmental systems and mainly analyzed the regulation mechanism of QS-based strategies for biofilm, granular sludge, functional bacteria, and biofouling control. The co-existences of multiple signal molecules in wastewater treatment (WWT) processes were also summarized, which provide basis for the future research on the QS mechanism of multiple signal molecules' interaction in WWT. This review would present some prospects and suggestions which are of practical significance for further application.